2015
DOI: 10.1016/j.childyouth.2015.03.022
|View full text |Cite
|
Sign up to set email alerts
|

Planned and unplanned terminations of foster care placements in the Netherlands: Relationships with characteristics of foster children and foster placements

Abstract: This study examined the role of placement and child characteristics in the unplanned termination of foster placements. Data were used from 169 foster children aged 0 to 20. Results showed that 35% of all foster placement terminations were unplanned. Outcomes of logistic regression analyses demonstrated that behavior problems, parenting stress and a non-Dutch ethnic background of the foster child increased the likelihood of a placement termination. Furthermore, risk accumulation contributed to unplanned termina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
1

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 37 publications
1
22
1
Order By: Relevance
“…Consistent with previous studies (Farmer, Lipscombe, & Moyers, 2005;Hurlburt et al, 2010;Jones & Morisette, 1999;McCarthy, Janeway, & Geddes, 2003), our study showed that a considerable group of foster parents had above average levels of parental stress . Although we found that foster parents' stress did not have an effect on foster children's internalising and externalising behaviour problems, we know from previous studies that parental stress can be negatively related to foster parents' motivation to continue fostering (Brown & Bednar, 2006;Farmer et al, 2005) and that parental stress therefore poses a risk for foster placement breakdown (Van Rooij, Maaskant, Weijers, Weijers, & Hermanns, 2015). Foster care professionals should be alert to foster parents' stress.…”
Section: Directions For Improvements In Foster Carementioning
confidence: 52%
“…Consistent with previous studies (Farmer, Lipscombe, & Moyers, 2005;Hurlburt et al, 2010;Jones & Morisette, 1999;McCarthy, Janeway, & Geddes, 2003), our study showed that a considerable group of foster parents had above average levels of parental stress . Although we found that foster parents' stress did not have an effect on foster children's internalising and externalising behaviour problems, we know from previous studies that parental stress can be negatively related to foster parents' motivation to continue fostering (Brown & Bednar, 2006;Farmer et al, 2005) and that parental stress therefore poses a risk for foster placement breakdown (Van Rooij, Maaskant, Weijers, Weijers, & Hermanns, 2015). Foster care professionals should be alert to foster parents' stress.…”
Section: Directions For Improvements In Foster Carementioning
confidence: 52%
“…Newton et al (2000) add to this that behavioural problems not only lead to a breakdown, but behavioural problems can also be the result of a breakdown and thus increasing the breakdown risk. In a Flemish (Vanderfaeillie et al, 2008) and a Dutch (Van Rooij et al, 2015) study, the association of previous placements and placement breakdown was not found. One Dutch study however (Strijker et al, 2008) did find a relationship between previous placements and breakdown.…”
Section: Foster Child Characteristics Associated With Breakdownmentioning
confidence: 94%
“…Research, including Flemish/Dutch studies, found a relationship between behavioural problems and mental health problems of the foster child, and breakdown. The evidence was most consistent for externalizing problems (Oosterman et al, ; Rock et al, ; Strijker et al, ; Van Rooij et al, ; Vanderfaeillie et al, ). Children with previous placements experience more placement breakdown (Oosterman et al, ).…”
Section: Foster Child Characteristics Associated With Breakdownmentioning
confidence: 95%
See 1 more Smart Citation
“…Children in foster care have substantially higher levels of behavioral and emotional problems than children in the general population (Burns et al 2004 ; Landsverk et al 2006 ; Maaskant et al 2014 ). These problems increase parental stress of foster parents (Vanderfaeillie et al 2012 ) and often lead to placement disruption (for a meta-analysis see Oosterman et al 2007 ; Van Rooij et al 2015 ). Placement disruption in turn increases the risk of consecutive unstable placements for foster children (e.g., Farmer 1996 ; Rubin et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%